Self-rated familiarity with autism spectrum disorders among practicing nurses: a cross-sectional study in the palestinian nursing practice - Ramzi Shawahna (BMC, 2021)
Abstract Background Autism spectrum disorders (ASDs) are one of the most prevalent neurodevelopmental disabilities of early childhood. Practicing nurses are in a key position to help patients with ASDs and/or their caregivers/families. This study was conducted to assess self-rated familiarity with ASDs among practicing nurses in Palestine. The study also aimed to identify the sociodemographic and practice variables that could predict high self-rated familiarity scores. Methods This was a cross-sectional study using a questionnaire. The study was conducted in the period between January 2019 and May 2019. The questionnaire collected: 1) the sociodemographic, pedagogic, and practice variables of the nurses, 2) their self-rated familiarity with signs and symptoms, treatment options, and community resources of ASDs, 3) their self-rated confidence in their abilities to provide counseling for parents/family/caregivers on the drugs prescribed for children/patients with ASDs and their potential adverse effects, and 4) their willingness to receive education/training on issues in ASDs. Results The questionnaire was completed by 357 practicing nurses. The practicing nurses self-reported inadequate familiarity with symptoms, treatment, and community resources of ASDs. The mean familiarity score was 35.8% (SD: 18.9%). The nurses also expressed low confidence in their ability to provide counseling services to caregivers/families of children with ASDs. About 75% of the nurses agreed that they could benefit from taking a continuing educational/training program in the area of ASDs and about 82% of the nurses agreed that the nursing school curriculum should include courses in the area of ASDs. The multiple linear regression model showed that higher familiarity scores were predicted by having longer practical experience, having a higher academic degree in nursing, and having a continuing educational course/program on ASDs. Conclusion Findings of this study highlighted inadequate familiarity with issues of ASDs among practicing nurses. Higher familiarity was predicted by the length of practical experience, higher academic degree in nursing, and having continuing educational course/program on ASDs. Specifically designed pedagogic interventions might be helpful in increasing familiarity of practicing nurses on ASDs. More investigations are still needed to evaluate if these interventions can improve familiarity and services provided to patients with ASDs.